Attitudes towards Patriotism and Patriotic Self-identity of Russian Students Youth in the Polarization of Russian Society - N.V. Murashcenkova; V.V. Gritsenko; N.V. Kalinina; V.V. Konstantinov; E.V. Kulesh; A.Y. Malenova; I.V. Malyshev (Социальная психология и общество, 2023)
Objective. The aim of the study is to analyze the salience and subjective significance of patriotic self-identity, and analyze the attitude towards patriotism among Russian student youth under conditions of polarization of Russian society. Background. Patriotic education of Russian youth, based on the potential of subject-to-subject interaction and implemented in the current polarization of Russian society, requires analysis of the patriotic self-identity of young people and their attitude towards patriotism. Study design. We carried out reflexive thematic analysis and qualitative content analysis of respondents' answers to open questions about the manifestations, advantages and shortcomings of patriotism. We evaluated the salience and subjective significance of patriotic self-identity among young people. Participants. University students from Moscow, Omsk, Penza, Saratov, Smolensk, Khabarovsk (670 Russians ages 18 to 25, M = 19,3, SD = 1,5, 21% of men) participated in the study. Data were collected in October 2022. Measurements. We used the shortened version of the questionnaire «Who am I?» by M. Kuhn, T. McPartland. We formulated the close-ended question to assess salience of patriotic self-identity, as in the Scale of Rapid Assessment of Ethnic Identity by N.M. Lebedeva, and open-ended questions for the assessment of attitude towards patriotism. Results. The subjective significance of patriotic self-identity for young people is low. One third of respondents are characterized by a fluctuating patriotic self-identity, one tenth of respondents feel very little patriotic, 6,4% of respondents do not feel patriotic at all. We discovered 5 types of attitudes among students towards patriotism. Recommendations were developed to increase the effectiveness of patriotic education of Russian students in the current conditions. Conclusions. There are barriers to the formation of a stable patriotic identity for a large part of the Russian student youth. Almost half of respondents identified a request for the development of constructive civic patriotism. In order to increase the effectiveness of patriotic education of young people in the current Russian context it is important to take into account the results of such research.